PERTANGGUNGJAWABAN KREDITUR ATAS HILANGNYA BARANG JAMINAN (STUDI DI KSP3 NIAS CABANG LAHUSA) - Rahmat Syukur Hulu (Jurnal Panah Hukum, 2023)
A creditor is a party that has a bill to another party for the property or services it provides where it is agreed that the second party will return property of the same value or service. The type of research used is a type of sociological legal research in the form of empirical studies to find theories regarding the working process of contract law. This type of research is also called field research, which examines the applicable legal provisions and what happens in reality in society. In conducting this research, the data needed are primary data obtained from observations, interviews and document studies. In collecting data, the authors obtain primary data directly from the field, from the community, and/or legal entities. The data analysis used is qualitative analysis, the data obtained is then compiled to achieve clarity of the problem to be discussed and the results are set forth in the form of a description. Based on the research findings and discussion, it can be concluded that the Creditor's Responsibility for Loss of Collateral in the KSP3 Nias Study Lahusa Branch is the responsibility of the creditor for the loss of collateral in KSP3, namely the KSP3 Nias Lahusa Branch is responsible for the loss of collateral submitted by a member or customer as the collateral for the loan is in the form of a land certificate, the responsibility of KSP3 Nias Lahusa Branch by replacing the collateral. In this case, all administrative matters related to the management of the new collateral are accounted for by the KSP3 Nias Lahusa Branch. The author suggests that KSP3 Nias Lahusa Branch be even more careful in carrying out work, and store collateral items safely so that members/customers do not feel disadvantaged